Modified cannulated screw fixation in the treatment of Pauwels type III femoral neck fractures: A biomechanical study. (April 2020) - Zhou, Lin; Lin, Jiaming; Huang, Anfei; Gan, Weidong; Zhai, Xu; Sun, Kai; Huang, Shiqing; Li, Zhizhong
Abstract: Background: Achieving satisfactory internal fixation for patients with Pauwels type III femoral neck fractures has become a critical problem. The purpose of this study was to compare a common standard internal reduction and fixation method for femoral neck fractures to the modified fixation methods. Methods: A computed tomography scan of the femur was performed to make a Three-dimensional (3D) model, and a fracture line was simulated in the femoral neck. 3Dfinite element analysis was carried out for different insertion methods of cannulated tension screws. Six healthy femur specimens were harvested from three formalin-fixed cadavers, and Pauwels type III femoral neck fracture was artificially created in bilateral femurs. The right side was treated with the inverted triangle construct method and the left side by the modified screw fixation method. After fixation, uniaxial compression and maximum load experiments on the bilateral femoral necks were carried out using the non-contact full-field dynamic strain measurement system (VIC-3D) on a pressure testing machine. Findings: Both 3D finite element analysis and biomechanical study showed that the modified screw fixation method(group D) provided better anti-shearing and anti-rotation properties for Pauwels type III femoral neck fractures, and offered better interfragmentary compression. Therefore, this modified screw fixation method can offer patients a better option for treatment of Pauwels type III femoral neck fractures. Interpretation: Changing the placement of the anterosuperior screw in the inverted triangle construct as perpendicular to the fracture line has the advantages in anti-shearing, anti-rotation and increasing interfragmentary compression. Highlights: This method is much better in anti-rotation and increasing fracture surface pressure. The modified fixation can withstand greater vertical shearing force. Modified screw fixation increases interfragmentary compression. The anterosuperior screw will be inserted perpendicular to the fracture line. Theoretically, this modified fixation creates the best primary healing condition.